2015
DOI: 10.1016/j.intimp.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the anti-inflammatory activity of Sutherlandia frutescens using murine macrophages

Abstract: Sutherlandia frutescens is a botanical widely used in southern Africa for treatment of inflammatory and other conditions. Previously, an ethanolic extract of S. frutescens (SFE) has been shown to inhibit the production of reactive oxygen species (ROS) and nitric oxide (NO) by murine neurons and a microglia cell line (BV-2 cells). In this study we sought to confirm the anti-inflammatory activities of SFE on a widely used murine macrophage cell line (i.e., RAW 264.7 cells) and primary mouse macrophages. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Our previous studies with microglial cells showed that ethanol extracts of Sutherlandia suppressed LPS- and IFNγ-induced ROS and NO production by inhibition of the JAK/STAT and ERK1/2 signaling pathways (Jiang et al, 2014). Similar anti-inflammatory activity was reported in murine macrophages, but did not appear to be mediated by sutherlandiosides or sutherlandins, which are glycosylated derivatives (Lei et al, 2015a). Moreover, our recent in vivo studies demonstrated that dietary Sutherlandia mitigates cerebral ischemia-induced neuronal damage, in part by attenuating p47phox and phospho-ERK1/2 expression in microglial cells(Chuang et al, 2014).…”
Section: Discussionsupporting
confidence: 68%
“…Our previous studies with microglial cells showed that ethanol extracts of Sutherlandia suppressed LPS- and IFNγ-induced ROS and NO production by inhibition of the JAK/STAT and ERK1/2 signaling pathways (Jiang et al, 2014). Similar anti-inflammatory activity was reported in murine macrophages, but did not appear to be mediated by sutherlandiosides or sutherlandins, which are glycosylated derivatives (Lei et al, 2015a). Moreover, our recent in vivo studies demonstrated that dietary Sutherlandia mitigates cerebral ischemia-induced neuronal damage, in part by attenuating p47phox and phospho-ERK1/2 expression in microglial cells(Chuang et al, 2014).…”
Section: Discussionsupporting
confidence: 68%
“…Importantly, we observed that treatment with SFE significantly diminished the expression of genes involved in signaling pathways associated with immune responses, such as: NF-κB, MAPK, and JAK-STAT. These findings are in agreement with our previous studies7,8 In this study, our use of RNA-seq provided insights into some of the possible molecular mechanisms through which Sutherlandia modulates macrophage function. For example, the treatment of SFE increased the expression of Nfkbia and Ikbke, which are two inhibitors of the NF-κB pathway.…”
supporting
confidence: 92%
“…The mechanisms for these putative medicinal properties of S. frutescens have not been investigated extensively. We and others have reported that ethanolic and aqueous extracts of this plant possess anti-inflammatory and immuno-stimulatory activities, respectively 6,7 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Meanwhile, the decrease of the articular diameter caused by the administration of the extracts of A. tequilana can be associated to the presence of active secondary metabolites like β-sitosterol glycoside, 3,7,11,15-tetramethyl-2-hexadecen-1-ol (phytol), octadecadienoic acid 2,3-dihydroxy-propyl ester, stigmasta-3,5-dien-7-one, cycloartenone, cycloartenol and fructans. β-Sitosterol glycoside, phytol, cycloartenone and cycloartenol isolated from Agave tequilana have been reported to present anti-inflammatory and immunomodulatory capacity in different inflammatory studies [ 19 , 20 , 21 , 22 ] and the articular anti-inflammatory effect of the fructans from A. tequilana could be due to the fact fructans participate in the activation of toll-like receptors type 2 and 4 (TLR 2and TLR4) that have also been related to have immunomodulatory and anti-inflammatory capacity which is independent to the prebiotic effect of said molecules [ 12 ].…”
Section: Discussionmentioning
confidence: 99%